Ultrafast probing of plasma ion temperature in proton–boron fusion by nuclear resonance fluorescence emission spectroscopy - T.-T. Qin; W. Luo; H.-Y. Lan; W.-M. Wang (Matter and Radiation at Extremes, 2022)
Aneutronic fusion reactions such as proton–boron fusion could efficiently produce clean energy with quite low neutron doses. However, as a consequence, conventional neutron spectral methods for diagnosing plasma ion temperature would no longer work. Therefore, finding a way to probe the ion temperature in aneutronic fusion plasmas is a crucial task. Here, we present a method to realize ultrafast in situ probing of 11B ion temperature for proton–boron fusion by Doppler broadening of the nuclear resonance fluorescence (NRF) emission spectrum. The NRF emission is excited by a collimated, intense γ-ray beam generated from submicrometer wires irradiated by a recently available petawatt (PW) laser pulse, where the γ-ray beam generation is calculated by three-dimensional particle-in-cell simulation. When the laser power is higher than 1 PW, five NRF signatures of a 11B plasma can be clearly identified with high-resolution γ-ray detectors, as shown by our Geant4 simulations. The correlation between the NRF peak width and 11B ion temperature is discussed, and it is found that NRF emission spectroscopy should be sensitive to 11B ion temperatures Ti > 2.4 keV. This probing method can also be extended to other neutron-free-fusion isotopes, such as 6Li and 15N.